10‐hydroxy‐2‐decenoic acid a bio‐immunomodulator in tissue engineering; generates tolerogenic dendritic cells by blocking the toll‐like receptor4. Issue 9 (27th February 2021) - Eslami‐kaliji, Farshid; Sarafbidabad, Mohsen; Kiani‐Esfahani, Abbas; Mirahmadi‐Zare, Seyede Zohreh; Dormiani, Kianoush
Abstract: Dendritic cells (DCs), in response to the biomaterials, utilize toll‐like receptors (TLRs) to become mature or tolerogenic through TLRs‐dependent signaling pathways, especially TLR4. Regarding the physicochemical properties of biomaterials, some of such signaling pathways are activated. Unsaturated fatty acids have been explored as an antagonist for TLRs and lead to the tolerogenic phenotype of DCs. Here we showed that, although cultured DCs on both chitosan and Alginate‐polyethyleneimine (Alg‐PEI) films became fully mature, 10‐hydroxy‐2‐decanoic acid (10‐HDA), an unsaturated fatty acid found in royal jelly, led to the tolerogenic immunophenotype of DCs on both films. The cultured cells on the films possessed iDCs‐like morphology in the presence of 10‐HDA. Moreover, 10‐HDA expressed lower levels of CD80, CD83, CD86, and HLA‐DR, a higher level of IL‐10, and lower level of IL‐12 in the cultured DCs on both films. Furthermore, HEK293T cells expressing only TLR4 (HEK‐TLR4 cells) were co‐cultured with LPS, a specific agonist for TLR4, and 10‐HDA. The 10‐HDA significantly reduced the expression of tumor necrosis factor‐a (TNF‐α) in the HEK‐TLR4 cells compared to treated only with LPS. These findings indicate that the 10‐HDA acts as an antagonist of TLR4; therefore, potentially can be used in autoimmune diseases and preventing the rejection of biomaterials implantation and allograft transplantation. Abstract :